2016-04-01T04:54:15+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
The balanced equation is:

Ca + 2 H2O --> Ca(OH)2 + H2

Solutions

1. First write the equation.
2. Second check for the number of atoms
3. Third Add coefficients

Ca+H2O -----> Ca(OH)2+H2
1 2 1 2 2

3(Ca+H2O3) -----> 3(Ca(OH)2+H2) We added our coefficients
3 6 1 -----> 1 2 2
3 + 6 + 6 -----> 3 + 6 + 6

3(Ca+H2O3) -----> 3(Ca(OH)2+H2)

2016-04-01T10:14:06+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Ca + 2 H2O -----> Ca(OH)2 + H2 This is the balance equation